Evaluating the Impact of Electronic Payment Channels on Sustainable Financial Inclusion in Nigeria - Okoyeuzu, Chinwe R.; Kalu, Ebere Ume; Ukpere, Wilfred Isioma (Journal of Reviews on Global Economics, 2019)
The underlining drives of many financial reforms were to motivate digital banking culture in order to achieve sustainable financial inclusion. It is not very clear the extent to which financial innovation reform has advanced financial inclusion in Nigeria. Similarly, some issues closely linked with digital finance have not been exhaustively addressed in the literature. This research paper therefore evaluated the effect that electronic payment channels had on financial inclusion in Nigeria. Quarterlized data obtained from the statistical bulletin of Central bank of Nigeria were used. The Autoregressive Distributed Lag Model was adopted and used for our estimation. Digital financing channels were not only significant but at same time positive with the financial inclusion variables under investigation. However, the observed financial inclusion may not have delivered access to all because the channels are elitist. The study advocates for a policy reform that takes care of structural rigidities to fully accommodate the excluded.